2019
DOI: 10.12788/jhm.3195
|View full text |Cite
|
Sign up to set email alerts
|

Critical Errors in Inhaler Technique among Children Hospitalized with Asthma

Abstract: Many studies have shown that improved control can be achieved for most children with asthma if inhaled medications are taken correctly and adequately. [1][2][3] Drug delivery studies have shown that bioavailability of medication with a pressurized metered-dose inhaler (MDI) improves from 34% to 83% with the addition of spacer devices. This difference is largely due to the decrease in oropharyngeal deposition, 1,4,5 and therefore, the use of a spacer with proper technique has been recommended in all pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
13
0
2
Order By: Relevance
“…A key component of asthma management is the use of respiratory inhalers to deliver quick-relief and controller medications [2]. Proper inhaler use is associated with fewer symptoms and emergency room visits, yet technique among children is poor [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A key component of asthma management is the use of respiratory inhalers to deliver quick-relief and controller medications [2]. Proper inhaler use is associated with fewer symptoms and emergency room visits, yet technique among children is poor [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…-Not shaking the pMDIs (21%-43.8%). 6,8,9 -Not breathing slowly (68.8%). 9 -Inhalation duration under 10 seconds (24.4%-34%).…”
Section: Discussionmentioning
confidence: 99%
“…This positive result for the emerging technology suggests that this type of learning would have great benefits for children with asthma. Using proper inhaler techniques give a better outcome for asthma sufferers [17], showing that basic education may provide teachable moments to address poor proficiency, especially for younger children. The Samady et al study found that nearly half of 113 hospitalised asthmatic children age 2-16 years demonstrated improper inhaler use, meaning the patients were not taking in the full dose of medication [17].…”
Section: Discussionmentioning
confidence: 99%